DISTRIBUTION OF CHLOROPHYL-A AND SEA SURFACE TEMPERATURE AND ITS INFLUENCE ON THE CATCH OF YELLOWFIN TUNA (Thunnus albacares) ON SERAYA BESAR ISLAND, EAST NUSA TENGGARA - Rafis Trisandi Dimu; Gilang Rusrita Aida; Achmad Kusyairi (Jurnal Perikanan Unram, 2024)
Determining fishing Ground (FG), fishermen on Seraya Besar Island still use traditional methods or only experience, so there is a need for a touch of technology and knowledge to predict fishing ground through the distribution of chlorophyll-a and the distribution of sea surface temperature (SST) so that fishing activities are more effective. and effective and efficient. Starting from this idea, the author wants to study the distribution of chlorophyll-A and sea surface temperature and their influence on the catch of yellowfin tuna (Thunnus Albacares) on Seraya Besar Island, East Nusa Tenggara. This research uses a descriptive method. Based on this research, the average distribution of chlorophyll-a from January to November 2023 in the fishing ground fishermen on Seraya Besar Island was 0.44 mg/m3. The average distribution of sea surface temperatures from January to November 2023 in the fishing ground for fishermen on Seraya Besar Island is 27.55 °C. Linear regression with the equation Y = 2618.120 + 1715.958 X1 - 99.329 X2 with an adjusted R2 value of 79%. The T test results show that the chlorophyll-a distribution variable has a significant partial effect. Meanwhile, the variable distribution of sea surface temperature has no significant partial effect on Yellowfin Tuna catches on Seraya Besar Island, East Nusa Tenggara. The results of the F test show that the variables of chlorophyll-a distribution and sea surface temperature have a significant simultaneous effect on the catch of Yellowfin Tuna on Seraya Besar Island, East Nusa Tenggara.